2016
DOI: 10.1016/j.tsf.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal treatment on solid–solid interface of hematite thin film synthesized by spin-coating deposition solution

Abstract: This work describes hematite films prepared by a spin-coating deposition solution (SCDS) method that is a sol-gel method derived technique. Hematite films were prepared at two heat treatment temperatures (500°C and 800°C) and the influence of thermal treatment on the photoelectrochemical performance was studied. In addition, since the SCDS method allows an optimal control of stoichiometry and impurity incorporation, hematite films modified with Zn 2+ and Sn 4+ were also prepared. The 800°C-treated hematite fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…However, a remarkable reduction in the peak intensity of the 3 mM Zn/5 Mm Ni NR sample was observed relative to other samples. This is in agreement with reports that the Raman intensities are directly proportional to crystallite sizes [ 55 , 56 ]. Moreover, a similar trend of results was noted for the crystallite sizes of the doped NR samples.…”
Section: Resultssupporting
confidence: 93%
“…However, a remarkable reduction in the peak intensity of the 3 mM Zn/5 Mm Ni NR sample was observed relative to other samples. This is in agreement with reports that the Raman intensities are directly proportional to crystallite sizes [ 55 , 56 ]. Moreover, a similar trend of results was noted for the crystallite sizes of the doped NR samples.…”
Section: Resultssupporting
confidence: 93%
“…No pronounced differences can be noticed between the morphology of the pristine FTO (Figure 2A) and the one modified with the Al 2 O 3 underlayer (Figure 2B), revealing the common irregular substrate surface. The pristine (Al 2 O 3 /H) and Nb‐modified (Al 2 O 3 /NbH) hematite films showed the typical grain shape obtained from a polymeric precursor solution 26,27 . Surface roughness (RSM) value estimated from an AFM image was of 30 nm for the FTO and 29 nm for the underlayer, whereas the Al 2 O 3 /H and Al 2 O 3 /NbH thin films decreased to 10 and 6 nm, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…It is also desirable that the photoelectrode design be based on a simple and scalable fabrication method, easily adaptable to the necessary modifications to reduce the photogenerated electron loss processes. Our group has been focusing on the understanding and experimental controls and developed new strategies to lower interfaces recombination in hematite photoanodes 25,26 . In particular, those prepared from polymeric precursor solutions have achieved benchmark values among the spin‐coated ones in 2019 27 .…”
Section: Introductionmentioning
confidence: 99%
“…As expected, our studies showed that the photocurrent improved with the film thickness that resulted from multiple depositions and/or by incorporating modifiers, such as Si 4+ , Zn 2+ , or Sn 4+ . Still, the maximum values were only 35 µA cm −2 , which was 0.3% of the theoretically predicted efficiency [150][151][152]. Some explanations for the low response were discussed, particularly the photogenerated charge recombination processes that were driven by the modifier segregation at the grain boundaries, which might act as recombination sites, and at the hematite-electrolyte interface, creating surface states.…”
Section: Polymeric-precursor Solution-based Methodsmentioning
confidence: 90%